Implications of ‘Low-cost, High-quality’ Education A Study of Low-fee Private Schools in Delhi - Kaur, Har Simrat (JOURNAL OF INDIAN EDUCATION, 2017)
The enactment of the Right of Children to Free and Compulsory Education Act, 2009, strengthens the commitment of the Government of India towards universalisation of elementary education. Additionally, India has witnessed a considerable progress with respect to access and enrolment in recent years. There has also been a rapid growth in alternate modes of private provision in the form of low-cost/low-fee private schools. Of late, low-fee private schools are being projected as a preferred choice for poor and disadvantaged families, who ignore government services and rather pay private schools, which offer cost-efficient education. This paper discusses the reason for low-fee private schools’ existence and finds if they provide low-cost, high-quality education. It empirically examines the implications of cost-efficiency in education with respect to two low-fee private schools in Delhi. First, it investigates the motivation for setting up these schools, their financial structure and second, whether these schools are able to meet the norms and standards necessary for delivering quality education as listed in the RTE Act, 2009. The paper highlights the concerns that crop up due to the low-cost provision in the private schooling sector. It argues that the underlying motivation driving these schools have direct implications on what is being offered by low-fee private schools.